WHEN HERITAGE BECOMES REAL: THE CASE OF THE INTERVENTION IN RESIDENCE N0 61 ON SAGRADO CORAÇÃO DE JESUS STREET IN LARANJEIRAS, SERGIPE/ BRAZIL - da Silva, Eder Donizeti (Seven Editora, 2025)
In October 2018, I received a writ of summons via electronic email to carry out an expert opinion of a Public Civil Action filed by the Federal Court of the 10th Court of the Judicial Section of the State of Sergipe, which contained Case N0 0802085-96.2016.4.05.8500; this process had as its object of action a property in the central historic perimeter of the city of Laranjeiras, 35 kilometers from the capital Aracaju. This property had been fined and embargoed by IPHAN under the allegation of changes in its architecture that caused damage to the historical and aesthetic value of that heritage urban complex, on the other hand, the owner alleged justifications for having carried out this intervention. For the instruction of the judicial decision, 8 questions were asked by the Honorable Federal Prosecutor responsible for the case, which had as a fundamental principle two imputations: Do the changes made to the property (construction of a recessed pavement in the upper part of the property) hurt the ambience of the architectural complex of the Historic Center of the Municipality of Laranjeiras or its surroundings? What technical solutions can be adopted to satisfactorily remedy the damage to the landscape of the Historic Center of Laranjeiras and its surroundings or the damage to its ambience caused by the construction of the recessed pavement? This article describes the methodology and ways sought to offer historical, theoretical and philosophical subsidies for the judicial decision of a process in dispute that revealed the veracity between use, property, right, social function, conservation, preservation and intervention when the harsh reality of when heritage becomes real emerged. DOI: https://doi.org/10.56238/sevened2025.018-005